2018
DOI: 10.1523/jneurosci.1432-18.2018
|View full text |Cite
|
Sign up to set email alerts
|

Claudin-1-Dependent Destabilization of the Blood–Brain Barrier in Chronic Stroke

Abstract: Recent evidence suggests that blood-brain barrier (BBB) recovery and reestablishment of BBB impermeability after stroke is incomplete. This could influence stroke recovery, increase the risk of repeat stroke, and be a solid substrate for developing vascular dementia. Although accumulating evidence has defined morphological alterations and underlying mechanisms of tight junction (TJ) changes during BBB breakdown in acute stroke, very little is known about the type of alterations and mechanisms in BBB "leakage" … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
96
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(99 citation statements)
references
References 40 publications
1
96
0
2
Order By: Relevance
“…The authors explained the reason for this contradictory finding is that the loss of barrier function was due to the reduced expression of occludin protein and not CLDN-1 [141]. Besides, the other study reported that high expression of CLDN-1 resulted in blood-brain-barrier (BBB) leakiness during post-stroke recovery and targeting of CLDN-1 by a CLDN-1 peptide improved the permeability of brain endothelial barrier [142]. So, these studies suggest that the upregulation of CLDN-1 cannot necessarily be universal to the increased barrier function and there might be other contributing factors that regulate these functions, and also we should not rule out the tissue specific expression of claudins as other possibility to their dichotomous roles.…”
Section: Claudin-1 and Tight Junction Barrier Functionmentioning
confidence: 99%
“…The authors explained the reason for this contradictory finding is that the loss of barrier function was due to the reduced expression of occludin protein and not CLDN-1 [141]. Besides, the other study reported that high expression of CLDN-1 resulted in blood-brain-barrier (BBB) leakiness during post-stroke recovery and targeting of CLDN-1 by a CLDN-1 peptide improved the permeability of brain endothelial barrier [142]. So, these studies suggest that the upregulation of CLDN-1 cannot necessarily be universal to the increased barrier function and there might be other contributing factors that regulate these functions, and also we should not rule out the tissue specific expression of claudins as other possibility to their dichotomous roles.…”
Section: Claudin-1 and Tight Junction Barrier Functionmentioning
confidence: 99%
“…In this regard, a recent study showed that claudin-1 replaces claudin-5 at the TJ of brain capillary endothelial cells during the regeneration phase after stroke. This replacement was associated with a weaker barrier [42]. Considering these data it could be speculated whether the strong expression of claudin-1 in the hCMEC/D3 may also be partly responsible for the weaker barrier of hCMEC/D3 cell layers.…”
Section: Discussionmentioning
confidence: 87%
“…For this reason, we have decided to conduct a comprehensive study on the transcript level in which all human claudins 1-25 were analyzed together with other TJ and BBB relevant ABC transporters in the most different conditions. Since first publications showed that the compensation of claudins can play an important role in the post stroke regeneration process [42] and that data on jointly regulated clusters of these targets are hardly known, it was decided to perform hierarchical cluster analysis. The obtained data can then be applied to propose possibly first coherent regulatory clusters.…”
Section: Discussionmentioning
confidence: 99%
“…Even the permeability at the choroid plexus, where claudin-3 is expressed, was unaffected by its deletion, although there may be a compensatory change in claudin-2 [63]. In a twist, Sladojevic et al [64] found that in chronic stroke there is an upregulation of claudin-1 that destabilizes (rather than stabilizes) the BBB leading to long-term low-level barrier leakiness that affects functional recovery.…”
Section: Claudins At the Cerebral Endotheliummentioning
confidence: 99%
“…Another approach to modulate the BBB has been to target brain endothelial junction proteins and a series of peptides have been developed that bind to claudins [172]. In 2019, one of those peptides was used to down-regulate claudin-1 at the BBB long-term after stroke as that particular claudin causes barrier instability [64]. Similarly, Yang et al [173] have used a peptide targeting E-cadherin to enhance brain uptake of eflornithine, a drug used to treat trypanosomiasis.…”
Section: Drug Deliverymentioning
confidence: 99%